Anaerobic co-digestion of the process water from waste activated sludge hydrothermally treated with primary sewage sludge. A new approach for sewage sludge management. (February 2020) - Villamil, J.A.; Mohedano, A.F.; San Martín, J.; Rodriguez, J.J.; de la Rubia, M.A.
Abstract: Hydrothermal carbonization (HTC) is a suitable technology for managing wastes with a high moisture content, providing a carbon-rich and high energy density material called hydrochar and a process water (PW) with significant organic matter content. The aim of this work was to develop a new approach to sewage sludge management involving anaerobic digestion (AD) of the PW of dewatered waste activated sludge (DWAS) with primary sewage sludge (PSS). The process was optimized by performing semi-continuous experiments with different feed mixture compositions (10% PW/90% PSS and 5% PW/95% PSS, on a COD basis), organic loading rates (OLR; 1.5 and 2.5 g COD L −1 d −1 ), and temperature regimes (mesophilic and thermophilic). The combination of mesophilic conditions, a 10% PW/90% PSS feed mixture and OLR of 1.5 g COD L −1 d −1 provided concentrations of volatile fatty acids <400 mg COD L −1 in addition to a methane yield (172 ± 11 mL CH4 g −1 CODadded ), 1.15 times the value for the control test (100% PSS). Therefore, the energy content of hydrochar from HTC of DWAS followed by AD of the process water with primary sewage sludge enhances the valorization of this renewable residue. Graphical abstract: Image 1 Highlights: Co-digestion of PW of DWAS + PSS is a new approach for sewage sludge management At 1.5 g COD L −1 d −1, 35 °C and 10% PW/90% PSS the CH4 yield is 15% over the control Increasing OLR from 1.5 to 2.5 g COD L −1 d −1 raised methane yield for 5% PW/95% PSS HTC of DWAS + AD of PW/PSS increased 4.4 times the energy of AD of mixed sludge